Students' Perceptions of Mathematical Physics E-Module on Multiple Integral Material - Astalini, Astalini; Darmaji, Darmaji; Kurniawan, Dwi Agus; Chen, Diki (Universitas Pendidikan Ganesha, 2021)
Mathematical physics is often considered a very difficult subject to study, one of the reasons that makes this happen is the lack of learning media that supports students. In addition, most of the existing media are in foreign languages, so in this case we need an Indonesian language learning media, namely the mathematical physics e-module on dual integral material. This study aims to see the level of students' perceptions of the mathematics physics e-module on the dual integral material that has been made. The approach of this study uses a mixed method with an explanatory model. The sampling technique in this research was purposive sampling with 68 research subjects active physics education students who contracted Mathematics Physics courses. The instrument used in this study was a student perception questionnaire with 15 questions and an interview sheet with 10 questions.. The data analysis used in this research is descriptive statistics. The results of physics education students' perceptions of the mathematics physics e-module of multiple internal material were categorized as good with a percentage of 66.17% and in the very good category with a percentage of 33.83%. From the results it can be seen that the mathematical physics e-module on dual integral material can support the learning process and increase student motivation.